Sulfur-Mediated Synthesis of Spherical Nickel Nanoparticles in a Chemical Vapor Reactor - Jo, Yong Su; Abdullaev, Mansurbek; Jin, Gwang Hwa; Swain, Bhabani Sankar; Lee, Byongpil; Eom, Hyung Sub; Min, Seok Hong; Kim, Seok Ki; Kim, Young Keun; Yang, Seung Min (ACS Omega, 2022)
In this study, we investigated the effect of the sulfur content in the NiCl2 precursor on the shape of nickel nanoparticles (Ni-NPs) prepared by chemical vapor synthesis. We obtained spherical Ni-NPs when using anhydrous NiCl2 mixed with NiSO4 or Na2SO4 with a molar ratio of 0.002 as precursors without changing any other process parameters whereas faceted Ni-NPs when using only anhydrous NiCl2 as a precursor. First-principles calculations supported experimental results, which showed that NiSO4-mixed NiCl2 and Na2SO4-mixed NiCl2 precursors favored the growth of spherical NPs.